2012
DOI: 10.1152/jn.01071.2011
|View full text |Cite
|
Sign up to set email alerts
|

Decision making by urgency gating: theory and experimental support

Abstract: It is often suggested that decisions are made when accumulated sensory information reaches a fixed accuracy criterion. This is supported by many studies showing a gradual build up of neural activity to a threshold. However, the proposal that this build up is caused by sensory accumulation is challenged by findings that decisions are based on information from a time window much shorter than the build-up process. Here, we propose that in natural conditions where the environment can suddenly change, the policy th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
341
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(370 citation statements)
references
References 66 publications
(124 reference statements)
28
341
0
1
Order By: Relevance
“…1d). We have shown support for this latter prediction in recent experiments, first using a task in which subjects made decisions based on discrete events (Cisek et al, 2009), and later using a variation of the randomdot task in which the motion coherence was changing during each trial (Thura et al, 2012). We have also shown that while monkeys make decisions about changing sensory information, neural activity in motor regions tracks evidence quickly (with old evidence leaking out within 200 ms), and combines it with a growing urgency signal .…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…1d). We have shown support for this latter prediction in recent experiments, first using a task in which subjects made decisions based on discrete events (Cisek et al, 2009), and later using a variation of the randomdot task in which the motion coherence was changing during each trial (Thura et al, 2012). We have also shown that while monkeys make decisions about changing sensory information, neural activity in motor regions tracks evidence quickly (with old evidence leaking out within 200 ms), and combines it with a growing urgency signal .…”
Section: Introductionsupporting
confidence: 55%
“…It is wellknown that RT distributions in decision-making tasks are very Including the low-pass filter of the UGM, however, does in fact render it responsive to changes in early evidence, and, overall, matches the behavioral data very well broad, and this can be explained either with large intra-trial noise -as in the DDM -or with large inter-trial variability -as in the LATER model (Carpenter & Williams, 1995) and the UGM (Cisek, Puskas, & El-Murr, 2009;Thura et al, 2012). Importantly, variability in the urgency signal also provides an alternative explanation for the shift in mean RT distributions reported by Winkel et al…”
Section: Interpreting Model Fits To Datamentioning
confidence: 77%
See 2 more Smart Citations
“…In two-choice situations with stationary evidence distributions, it is optimal to accumulate information until one of two fixed boundaries is reached (Wald, 1945(Wald, , 1947Stone, 1960;Edwards, 1965;Bogacz et al, 2006). However, in situations where there is a stochastic response deadline (Frazier & Yu, 2008) or one is limited by total time and not number of trials in a task, it is optimal to allow response boundaries to collapse, reflecting the diminishing returns on collecting additional evidence (Thura, Beauregard--Racine, Fradet, & Cisek, 2012;Drugowitsch, Moreno-Bote, Churchland, Shadlen, & Pouget, 2012). The memory evidence posited by our model can be seen as imposing a kind of stochastic deadline, since no new information accrues once the probe is saturated with features.…”
Section: Collapsing Boundary Considerationsmentioning
confidence: 99%